Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In other words,

$$\text{Var}\left\{ [W(t) - W(s)]^2 \right\} = \mathbb E \left\{ (W(t) - W(s))^4 \right\} - \left[ E\left\{ (W(t) - W(s))^2 \right\} \right]^2 $$

How is this equal to $(t-s)^2$ given that $\mathbb E[[W(t)-W(s)]^2] = t-s$?

share|cite|improve this question

Since for $Z\sim \mathcal (0, \sigma ^2)$, we have $\mathbb E \{Z^4\} = 3 \sigma ^4$ (, we can deduce that

\begin{align}\text{Var}\left\{ (W(t)-W(s))^2 \right\} &= \mathbb E \left\{ (W(t)-W(s))^4 \right\} - E\left\{ (W(t)-W(s))^2 \right\} ^2 \\&=3 (t-s)^2 - (t-s)^2 = 2(t-s)^2 \end{align}

share|cite|improve this answer

$$\text{Var}((W_t-W_s)^2) = \text{Var}(W_{t-s}^2) = \mathbb{E}\left[(W_{t-s}^2-(t-s))^2 \right] \stackrel{\ast}{=} (t-s)^2 \cdot \underbrace{\mathbb{E}((W_1^2-1)^2)}_{2} = 2(t-s)^2$$

In $(\ast)$ we used scaling property, i.e. $W_{t-s} \sim \sqrt{t-s} \cdot W_1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.